Prevalence of Cryptococcal Antigen and Outcomes in People With Human Immunodeficiency Virus in Honduras: A Cohort Study. (13th November 2020) - Zuniga-Moya, Julio C; Romero-Reyes, Luis Enrique; Saavedra, Emilio Barrueto; Montoya, Sandra; Varela, Diana; Borjas, Mitchel; Cerna, Alicia; Bejarano, Suyapa; Martinez, Paola; Lujan, Karen; Erazo, Karen; Lainez, Isis; et al.
Abstract: Background: Cryptococcal meningitis is a major cause of death among people with human immunodeficiency virus (PWH). Cryptococcal antigen (CrAg) testing of asymptomatic patients is an important public health measure to reduce mortality in high-incidence areas. However, limited data exist on CrAg prevalence in Central America. Methods: We conducted a prospective cohort study at the 2 largest human immunodeficiency virus (HIV) clinics and hospitals in Honduras. Cryptococcal antigen in serum and cerebrospinal fluid was performed in individuals with HIV who had CD4 ≤100 cells/mm 3 between 2017 and 2018. After CrAg testing, individuals were observed for 12 months to assess mortality using adjusted Cox proportional hazard models. Results: A total of 220 PWH were tested for CrAg, 12.7% (n = 28) of which tested positive. Cryptococcal antigen prevalence was higher among hospitalized individuals in 40% (n = 10 of 25) of the cases. The proportion (35.8%) of individuals taking antiretroviral therapy was significantly ( P  < .01) lower among those who tested positive for CrAg. Overall mortality among the cohort was 11.4% (n = 25 of 220) by 12 months. Cryptococcal antigen-positive cases were at a significantly higher risk of death (adjusted hazard ratio, 2.69; 95% confidence interval, 1.07–6.84) compared with CrAg-negative participants. Conclusions: Cryptococcal antigen prevalence in Honduras was high among PWH. Moreover, individuals who tested positive for CrAg testing were at a higher risk of death. Systemic CrAg of PWH with a CD4 ≤100 cells/mm 3 should be routinely performed in Central America. Abstract : This cohort study shows a high prevalence of CrAg among Honduran individuals with HIV. Individuals testing CrAg positive were at a higher risk of death during a 12-month period compared with individuals who tested CrAg negative.